Belenus, Cybele, and Attis: Echoes of their Cults through the Centuries - Šašel Kos, Marjeta (Studia mythologica Slavica, 2022)
There are two interesting cases of the worship of Roman period deities in the north-eastern Italian and Pannonian regions, which in one way or another seem to have survived through the early medieval to modern times. The first is the cult of Belenus, the well-known Celtic and most notably Norican and Aquileian god. The second case is that of Cybele and Attis, the so-called eastern deities, whose cult became highly influential in the mentioned areas – as well as elsewhere – in the second and third centuries AD. Interestingly, a deity called “holy Belin” was documented in the second half of the 19th century in the area of Tolmin in Slovenia (the hinterland of Aquileia), as a traditional folk belief. In Pannonia, traces of the cult of Cybele and Attis seem to have survived from antiquity in Prekmurje and Porabje (Slovenia, Hungary), reflected in the unusual and still existing custom of the “wedding with a pine-tree”.